Economy, family, and society from Rome to Islam a critical edition, English translation, and study of Bryson's Management of the estate - Swain, Simon (Cambridge University Press, 2013)
Bryson's Management of the Estate (Oikonomikos Logos) offers advice on the key private concerns of the Roman elite: getting rich, managing slaves, love and marriage, bringing up children. This new edition of the text together with the first English translation will appeal to Roman social and economic historians, students of imperial Greek literature and all those interested in the development of Greco-Roman thought in the Islamic empire of the Middle Ages.